2019
DOI: 10.1007/978-3-319-46425-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Living on Cold Substrata: New Insights and Approaches in the Study of Microphytobenthos Ecophysiology and Ecology in Kongsfjorden

Abstract: Organisms in shallow waters at high latitudes are under pressure due to climate change. These areas are typically inhabited by microphytobenthos (MPB) communities, composed mainly of diatoms. Only sparse information is available on the ecophysiology and acclimation processes within MPBs from Arctic regions. The physico-chemical environment and the ecology and ecophysiology of benthic diatoms in Kongsfjorden (Svalbard, Norway) are addressed in this review. MPB biofilms cover extensive areas of sediment. They sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 105 publications
0
14
0
Order By: Relevance
“…The few data available on benthic diatoms from polar regions confirm a high photophysiological plasticity to acclimate to the prevailing, often very low light conditions [ 10 , 11 , 21 , 22 , 23 , 67 ]. In addition, this wide photophysiological plasticity seems to be a rather general trait of many diatom species [ 24 ], as documented in species from Arctic Kongsfjorden [ 27 ], but also in numerous species from the shallow waters of the temperate Baltic Sea [ 48 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few data available on benthic diatoms from polar regions confirm a high photophysiological plasticity to acclimate to the prevailing, often very low light conditions [ 10 , 11 , 21 , 22 , 23 , 67 ]. In addition, this wide photophysiological plasticity seems to be a rather general trait of many diatom species [ 24 ], as documented in species from Arctic Kongsfjorden [ 27 ], but also in numerous species from the shallow waters of the temperate Baltic Sea [ 48 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…While Arctic benthic diatoms can be characterized as eurythermal and psychrotolerant microalgae with growth optima at around 15 °C [ 26 , 27 ], this seems to be in sharp contrast to their Antarctic counterparts, which show stenothermal and psychrophilic traits [ 28 ]. Psychrophilic and psychrotolerant species can be physiologically distinguished, as the former can survive at freezing temperatures but will die at more moderate temperatures [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Wulff et al (2008) found degradation of pigments from a natural benthic diatom community from Antarctica after "only" 64 days in darkness. Similarly, Karsten et al (2019) reported that pigments in the benthic diatom Surirella cf. minuta from Kongsfjorden began to degrade after a few days in darkness.…”
Section: Discussionmentioning
confidence: 84%
“…Polar macrophytes must show a high potential for dark survival, as they must live up to 4 months (or even more) in complete darkness (Schlie et al, 2011), but the physiological, biochemical, and molecular mechanisms behind this adaptation for dark survival are still poorly understood (Karsten et al, 2019). Some mechanisms for long-term dark survival have been described in polar diatoms (McMinn and Martin, 2013), including the utilization of stored products (Palmisano and Sullivan, 1983;Schaub et al, 2017), the reduction of respiration and metabolic rates (Peters and Thomas, 1996), the formation of resting stages (reviewed by McQuoid and Hobson, 1996), or facultative heterotrophy (Hellebust and Lewin, 1977;Armbrust et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, studies on algae exposed to prolonged dark periods were mainly focused on the growth patterns (Lüning, 1969;Smayda and Mitchell-Innes, 1974;Chapman and Lindley, 1980;Dunton, 1985), physiological performances and biochemical mechanisms (Weykam et al, 1997;Lüder et al, 2002;Karsten et al, 2019). Mcminn and Martin (2013) concluded several strategies for algae to survive long periods of darkness.…”
Section: Introductionmentioning
confidence: 99%